Building Children's Social Skills Through Picture Story Books - Sinamo, Junita; Panjaitan, Lestari Sri Wahyuni; Butar Butar, Mei Lastri E.F. (PRODI PKAUD, IAKN TARUTUNG, 2024)
This research explains the role of picture books in developing children's social skills. Through a careful literature review, this research identified several key aspects, ranging from understanding social skills to practical strategies for incorporating picture books into children's education. Reading picture books can develop children's social skills such as empathy, critical thinking skills, communication, cooperation and tolerance. Picture books allow children to feel like they will act out emotions as characters in the story., understand the plot of the story, identify problems and find solutions, and learn about cooperation and respecting differences. Practical strategies such as reading aloud, using stories as starting points for conversations, and using stories as examples to resolve conflicts can help maximize the benefits of picture books for children's learning. Incorporating picture books into a child's education helps children develop social skills that are important for life success while providing a fun and meaningful learning experience for early childhood. Keywords: Social Skills, Early Childhood, Picture Story Books